2023
DOI: 10.1371/journal.pone.0280588
|View full text |Cite
|
Sign up to set email alerts
|

The effect of contraceptive access reform on privately insured patients: Evidence from Delaware Contraceptive Access Now

Abstract: Background Many states are implementing comprehensive programs aimed at reducing persistent barriers to contraceptive care. Evidence on the effectiveness of these programs is essential for practice improvement and policy development. Objective To evaluate changes in the probability of initiating a contraceptive method by women with employer sponsored insurance after implementation of Delaware Contraceptive Access Now (DelCAN), a statewide initiative that aimed to increase access to long-acting reversible con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…For example, despite potential confounding from pre‐existing disparate trends, evaluations from Colorado provide suggestive evidence of abortion effects in patients under the age of 20 13 . Other studies on DelCAN also found larger effects on LARC uptake among teenagers 24,25 . However, as we show in Appendix Figure A4, the trend in abortion rates within Delaware was generally similar for younger and older patients, which is not suggestive of heterogeneous effects by age.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…For example, despite potential confounding from pre‐existing disparate trends, evaluations from Colorado provide suggestive evidence of abortion effects in patients under the age of 20 13 . Other studies on DelCAN also found larger effects on LARC uptake among teenagers 24,25 . However, as we show in Appendix Figure A4, the trend in abortion rates within Delaware was generally similar for younger and older patients, which is not suggestive of heterogeneous effects by age.…”
Section: Discussionsupporting
confidence: 50%
“…There are several possible explanations for why we did not observe strong evidence of an effect on abortion from DelCAN, despite previous evidence that the program increased LARC use. First, we expected that effects on abortion would be contemporaneous with changes in contraceptive use observed in other studies 23–25 . However, program effects in Delaware may grow over time as providers continue to adapt to new practice styles and patients become more aware of available services, especially considering that the program components were gradually introduced over 2015–2020.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations